2002
DOI: 10.1007/s11661-002-0388-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of au plating on small-scale resistance spot welding of thin-sheet nickel

Abstract: The effects of Au plating on joint formation and joint strength in small-scale resistance spot welding (SSRSW) of Ni sheets have been investigated using tensile-shear testing, optical microscopy, scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). The results show that the mechanisms of the joint formation during the welding of Au-plated Ni sheets involve solid-state bonding, brazing, and fusion welding. The comparison between SSRSW of Au-plated Ni and bare Ni sheets and large-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 9 publications
0
45
1
Order By: Relevance
“…15) Furthermore during the first two cycles of resistance welding the molten coating is pushed away from the FZ. 16) …”
Section: Methodsmentioning
confidence: 99%
“…15) Furthermore during the first two cycles of resistance welding the molten coating is pushed away from the FZ. 16) …”
Section: Methodsmentioning
confidence: 99%
“…Depending on joining process employed (fusion welding, brazing/soldering, and solid state bonding), roughly three approaches are used to eliminate surface contamination (mainly oxide films), which is the greatest single impediment to metallurgical bonding between two metallic surfaces. 14,17,18) One is the use of a chemical flux, which removes oxide films from surfaces being jointed (as in brazing and soldering): this is not relevant in this work since no fluxes were used. Another approach is by melting and/or washing away of oxide films, as in fusion welding, when adjacent base metal becomes molten.…”
Section: Welding Mechanismmentioning
confidence: 99%
“…Previous work on RMW of crossed fine Ni wires using an alternating-current supply showed that the welding mechanism based on solid-state bonding with transient liquid phase. 13) These mechanisms of joint formation are significantly different from those in RMW of the Ni sheets where a fusion nugget is formed, 14) probably due to different geometric shape of the specimens resulting in different interfacial phenomena during welding.…”
Section: Introductionmentioning
confidence: 99%
“…Current literature on microwelding of crossed wires focuses on RMW processes such as the joining of Ni sheets, bare and Au-plated Ni wires, 316 LVM SS, and 304 SUS SS [3,4,7,8]. To date, only limited literature exists detailing the research on laser microwelding of crossed wire, this is especially true for dissimilar materials.…”
Section: Introductionmentioning
confidence: 99%